2020
DOI: 10.1016/j.neubiorev.2019.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Bilingual language processing: A meta-analysis of functional neuroimaging studies

Abstract: Notwithstanding rising interest, a coherent picture of the brain's representation of two languages has not yet been achieved. In the present meta-analysis we analysed a large number of functional neuroimaging studies focusing on language processing in bilinguals. We used activation likelihood estimation (ALE) to enucleate activation areas involved in bilingual processing and control of different types of linguistic knowledge -lexico-semantics, grammar, phonology -in L1 and L2. Results show that surprisingly, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(81 citation statements)
references
References 215 publications
(187 reference statements)
2
79
0
Order By: Relevance
“…Moreover, being bilingual is not a static characteristic or an ‘on/off’ experience. As we have noted, recent research indicates that when one considers bilingualism as the spectrum of dynamic experiences it is, multiple variables are shown to affect the occurrence and degree of cognitive and neuroanatomical adaptations (e.g., Bak, 2016b; Bialystok, 2016; Luk & Bialystok, 2013; Li et al, 2014; De Cat, Gusnanto & Serratrice, 2018; Gullifer et al, 2018; Dash et al, 2019; Beatty-Martínez et al, 2019; DeLuca et al, 2019; 2020; Sulpizio, Del Maschio, Fedeli & Abutalebi, 2020b). The elusiveness of bilingual effects, then, could be related, at least partially, to the polysemous nature of the term ‘bilingual’, referring to very different populations across studies.…”
Section: The Heterogeneity Of the Term ‘Bilingual’ And Its Implicatiomentioning
confidence: 99%
“…Moreover, being bilingual is not a static characteristic or an ‘on/off’ experience. As we have noted, recent research indicates that when one considers bilingualism as the spectrum of dynamic experiences it is, multiple variables are shown to affect the occurrence and degree of cognitive and neuroanatomical adaptations (e.g., Bak, 2016b; Bialystok, 2016; Luk & Bialystok, 2013; Li et al, 2014; De Cat, Gusnanto & Serratrice, 2018; Gullifer et al, 2018; Dash et al, 2019; Beatty-Martínez et al, 2019; DeLuca et al, 2019; 2020; Sulpizio, Del Maschio, Fedeli & Abutalebi, 2020b). The elusiveness of bilingual effects, then, could be related, at least partially, to the polysemous nature of the term ‘bilingual’, referring to very different populations across studies.…”
Section: The Heterogeneity Of the Term ‘Bilingual’ And Its Implicatiomentioning
confidence: 99%
“…(word identification system), and the SMA [−6, 20, 49] (task/decision system), as defined by recent studies (Hsieh et al, 2017;Sulpizio et al, 2020). Activation patterns were further extracted to compare cognitive processing for each word type (Figure 4).…”
Section: Brain Imaging Resultsmentioning
confidence: 99%
“…More precisely, longer sentences or a more complex auditory story might generate more MFG brain activation in the process of comprehending the English story. In a recent study, Sulpizio et al (2020b) found that the larger involvement of dorsal-stream PFC resources in difficult rather than easy conditions could be related to the additional demands of phonological computation and cognitive decoding in L2. Thus, the more difficult auditory story engaged more brain networks for language processing and cognitive processing, to a certain extent.…”
Section: Brain Activation Pattern For Auditory Story Comprehensionmentioning
confidence: 98%